Duck production - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
'Duck production: science and world practice', edited by David J.Farrell and Paul Stapleton, 430pp, ISBN 0 85834 626 5.